2020
DOI: 10.1080/02671522.2020.1736614
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the dynamics of collegial networks in relation to beginning teachers’ job attitudes

Abstract: Previous research has pointed at the pivotal role of professional collegial support relationships to keep beginning teachers in the profession. In this study, we build on previous research by using follow-up mixed-method social network data to explore (1) to what extent, in what ways and for which reasons beginning teachers' work-related network (position) changes throughout a school year, and (2) how the network (position) of beginning teachers influences their job attitudes, as important precursors of teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…A range of studies have highlighted the importance of social network formation for learning for ECAs (Pataraia et al, 2014;Rehm et al, 2014;Thomas et al, 2020a). For example, Pataraia et al (2014) investigated the informal networks of teaching academics using a SNA approach.…”
Section: Social Network Theory Multiple and Multi-dimensional Transimentioning
confidence: 99%
See 4 more Smart Citations
“…A range of studies have highlighted the importance of social network formation for learning for ECAs (Pataraia et al, 2014;Rehm et al, 2014;Thomas et al, 2020a). For example, Pataraia et al (2014) investigated the informal networks of teaching academics using a SNA approach.…”
Section: Social Network Theory Multiple and Multi-dimensional Transimentioning
confidence: 99%
“…Pataraia et al (2014) found that the personal networks were strongly localized to the academics' departments and disciplines, and were dependent on whether the majority of the members knew each other well. Similarly, in a schooling context a range of studies have found that with whom an earlycareer teacher networks is essential for successful transition (Thomas et al, 2019(Thomas et al, , 2020a. For example, in a year-long study of 10 beginning teachers in Belgium (Thomas et al, 2020b) combining four SNA measurements with in-depths interviews with both beginning teachers and their colleagues indicated that many early-career teachers went through diverse complex transitions.…”
Section: Social Network Theory Multiple and Multi-dimensional Transimentioning
confidence: 99%
See 3 more Smart Citations